The role of the united nations security council in protecting human rights - سالم حوة (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2021)
The international protection of human rights has been the origin of an international legal order called the international human rights law.This new branch emerged from many multi-lateral conventions defining the various individual and collective rights human beings deserve. The realization of these rights required the active contribution of the united nations and its organs. The security council may partipated actively in respecting human rights when dealing with situation threatening peace and security through ;united nations sanctions, strong peace missions and even the criminal prosecution